Analisis Butir Soal HOTS Pilihan Ganda Pada Elemen Komputer Akuntansi Di SMKN 10 Surabaya Menggunakan Aplikasi Anates - Ahmad firandhika; Kartika Dwi Apriliyanti; Andini Kasih Agus Saputri; Luqman Hakim; Vivi Pratiwi (CV. Ulil Albab Corp, 2024)
This study aims to analyze the quality of HOTS (Higher Order Thinking Skills) multiple-choice items in the Accounting Computer Elements Phase F at SMKN 10 Surabaya, administered to 11th-grade students. The research was conducted using the ANATES application to evaluate the validity and reliability of the test items, as well as to identify the difficulty level, discrimination power, and consistency of the questions. The method used in this study is descriptive statistical analysis by collecting data from the student exam results, which consists of multiple-choice items measuring critical, analytical, and evaluative thinking skills in the context of Accounting Computer Elements material. The analysis results indicate that almost all the items have an appropriate difficulty level and sufficient discrimination power, though some questions need to be revised to improve the quality of the assessment. Furthermore, the overall reliability of the test items is deemed adequate for measuring student competence. This study is expected to provide recommendations for improving future exam questions and contribute to enhancing the quality of learning assessments at SMKN 10 Surabaya, particularly in the field of Accounting Computer Element.